Enhancement of WRF Model Using CUDA - Maharjan, Ashish; Shakya, Ashish (Interdisciplinary Journal of Innovation in Nepalese Academia, 2022)
The main aim of this paper is to implement and run WRF (Weather Research and Forecasting) model on Graphical Processing Unit (GPU) with the help of NVidia’s CUDA (Compute Unified Device Architecture) in a normal machine. Without GPU, the model needs high-end systems to be executed smoothly. For this, CUDA code is executed for a particular microphysics module to create an object file which is then added to the WRF model. Later the object file is executed on the GPU with the help of CUDA.